An investigation into the performance and persistence of actively managed equity mutual funds in the U.S - Wu, Wendi (2018)
This paper aims to investigate the performance of U.S equity mutual funds under active management to find whether fund managers can gain excess returns by superior stock selection and market timing abilities using data from 2007 to 2017. The Capital Asset Pricing Model (CAPM) and four-factor model are used to analyse fund performance. A Market timing model developed by Treynor and Mazuy (1966) is applied for market timing ability analysis. Furthermore, the persistence of mutual fund performance is investigated by forming four equally weighted portfolios based on the previous period’s performance.